The effect of bilingual mode of instruction on pupils’ academic achievement in social studies in Oyo state primary schools (2013)
Bilingual mode of instruction is considered very important at the primary level of education. This becomes very necessary due to the multiplicity of languages evident in some countries like Nigeria. Consequently, bilingual situation is observed in primary schools at certain levels of primary education. Pupils learn and are taught in English language which is quite different from their ethnic languages. The study therefore investigated the effect of bilingual mode of instruction on pupils’ achievement in Social Studies. The study adopted quasi- experimental approach. Stratified and simple random sampling was used to draw a sample of200 basic six (6) pupils from four schools (two rural and two urban schools) for the study. The instrument (Social Studies Achievement Test (SSAT) was developed by the researchers and used for data collection. The instrument was subjected to Kuder Richardson 21 with reliability coefficient of 0.82. The result of the study show that the bilingual mode of instruction has significant effect on achievement of pupils in Social Studies F (1.191) - 72.738, p< 0.05 Partial Eta Square n?= .276. Therefore the effect size (27.6%) is moderate. Hence, mode of instruction accounted for 27.6% of the total variance in the pupils’ achievement in Social Studies.